Relationship between Patients, Visitors’ Violence and Emergency Nurses’ Work Productivity - Abdou, Fayza Ahmed; Baraka, Azza Abd Elrazek (International Journal of Innovative Research in Medical Science, 2018)
Background: Violence in the health care setting affects the employee, employer, and patients. Emergency department (ED) nurses experience physical assaults at the highest rate of all nurses which may affect their productivity and job satisfaction. Objective: assess the relationship between patients and visitors’ violence and emergency nurses work productivity. Research question: what is the relationship between patients and visitors' violence and emergency nurses work productivity? Research design: descriptive research design was used in this study. Setting: This study was conducted in emergency department of Assuit Main University Hospital cardiopulmonary resuscitation unit (CPR) and trauma unit. Subjects: A convenient sample of approximately 100 emergency care nurses were in this study and the period of data collection from January 2017 to April 2017. Results: more than two third of nurses (68%) had a negative effect on their work productivity after exposure to violence. Also, the majority of them feels emotionally exhausted and don’t be able to continue their work. Conclusion: emergency nurses were predisposed to work violence from patients and their families which affect negatively their productivity of work and ability to continue in their career.